2010
DOI: 10.1007/s11111-010-0113-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of gender on climate change knowledge and concern in the American public

Abstract: This study tests theoretical arguments about gender differences in scientific knowledge and environmental concern using 8 years of Gallup data on climate change knowledge and concern in the US general public. Contrary to expectations from scientific literacy research, women convey greater assessed scientific knowledge of climate change than do men. Consistent with much existing sociology of science research, women underestimate their climate change knowledge more than do men. Also, women express slightly great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

86
449
10
18

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 802 publications
(563 citation statements)
references
References 42 publications
86
449
10
18
Order By: Relevance
“…This agrees with earlier findings that women express more scientifically accurate climate change knowledge and less climate scepticism than men 7,9,12 . Nevertheless, the result contrasts with studies using closed questions, where women tend to be more concerned than men 12 . In our study, this elevated concern, confirmed by the closed questions of our own poll, does not translate into a higher likelihood of using words related to future impacts.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This agrees with earlier findings that women express more scientifically accurate climate change knowledge and less climate scepticism than men 7,9,12 . Nevertheless, the result contrasts with studies using closed questions, where women tend to be more concerned than men 12 . In our study, this elevated concern, confirmed by the closed questions of our own poll, does not translate into a higher likelihood of using words related to future impacts.…”
supporting
confidence: 93%
“…There are tendencies among individuals with university education to choose responses that fit the Future/Impact frame rather than the Money/Consumption frame, but only the effect on the latter topic is borderline significant. This is somewhat surprising given that education usually predicts significant variation in opinion 7,8,10,12 , but agrees with Shwom's study using open-ended survey questions 17 . Thus, although educational effects clearly exist in closed questions on climate change, education has less of an effect in determining what people think of as important in the context of climate change.…”
supporting
confidence: 76%
“…In addition, females polluted more than males. This result is quite unexpected, since studies have found that climate change often burdens women more than men, that marginalization of women makes them more vulnerable to climate change impacts than men, and that women are generally more concerned about climate change than men (Korkala, Hugg, & Jaakkola, 2014;McCright, 2010;Habtezion, 2012;Olsson et al, 2014). 10 Furthermore, the subjects who were of the opinion that it is unfair for Africa to reduce emissions polluted more (kept 2.7 more red cards) than their counterparts who thought it was fair.…”
Section: Resultsmentioning
confidence: 99%
“…Income has been positively related to knowledge of climate change, but more strongly positively linked to self-reported knowledge of climate change (McCright, 2010). Similarly, though residential energy use increases with income, it is still possible to expect higher income to be linked to higher reported energy saving behaviour (McCright, 2010).…”
Section: The Influence Of Demographic Factors On Environmental Behavimentioning
confidence: 99%